Entrepreneurship and new value creation : the dynamic of the entrepreneurial process - Fayolle, Alain (Cambridge University Press, 2007)
Why do some individuals decide they want to create businesses and then actually do so? Why do others decide against this course of action, even though they appear to have what it takes to succeed? These two questions were among the first that researchers in the field of entrepreneurship tried to answer. Today, it seems that the problem is much more difficult to solve than it first appeared thirty years ago. The venture creation phenomenon is a complex one, covering a wide variety of situations. The purpose of this book is to improve our understanding of this complexity by offering both a theory of the entrepreneurial process and practical advice on how to start a new business and manage it effectively. Entrepreneurship and New Value Creation is a highly original, research-driven book that will appeal to graduate students, researchers and reflective practitioners concerned with the dynamics of the entrepreneurial process.